Multi-level factors associated with low dose computed tomography lung cancer screening in the United States - Tseng, Tung-Sung; Li, Chien-Ching; Lin, Hui-Yi; Witmeier, Kelsey N; Zeng, Chaoyi; Chiu, Yu-Wen; Celestin, Michael D; Trapido, Edward J (Journal of the National Medical Association, 2025)
Low-dose computed tomography (LDCT) screening is recommended for high-risk smokers to decrease lung cancer-related mortality and increase prognosis. In the U.S., the uptake of LDCT screening among eligible smokers is suboptimal. The impacts of social-environmental and individual factors on LDCT screening uptake using nationally representative dataset recommendations are understudied. The current study investigated multi-level factors associated with LDCT screening using national data. The 2017-2021 Behavioral Risk Factor Surveillance System (BRFSS) data, social determinants of health (SDOH) and other state-level variables (Medicaid expansion status and the number of screening facilities using American Lung Association (ALA) 's State of Lung Cancer) were applied. Our study outcome variance was LDCT screening among study participants who met the U.S. Preventive Services Task Force guidelines for lung cancer screening. The final study sample consisted of 15640 respondents from 29 states. All analyses were weighted to account for the complex sampling design applied in BRFSS. The overall utilization rate of LDCT screening is only 18.4%. The LDCT screening rate varied by state (6.2 -31.1%). LDCT screen rates were not significantly associated with the number of lung cancer screening facilities (r=0.02, p=0.909) but were positively associated with the number of lung cancer screening facilities per 10,000 smokers (r=0.67, p<0.001). Among the respondents, individuals who were employed, never married, reported good health status, did not have primary care physicians, economic concerns like low income, did not have routine checkups, and did not have certain chronic conditions (i.e. cancer, asthma, COPD) had a lower utilization rate of LDCT screening compared with their counterpart. The use of LDCT screening among eligible smokers remains low. Enhancing access to care for high-risk individuals, promoting services to diverse racial and socioeconomic groups, and expanding Medicaid coverage to incorporate annual LDCT screening can be used to guide future lung cancer screening programs.